Millennial students' metalinguistic knowledge on headlines Using Grammaticality Judgment Test - Betty E. Tuttle; Leonardo O. Munalim (Universitas Syiah Kuala, 2022)
Amid the proliferation of online news portals, there is a felt need for a reinvestigation of the millennial students' metalinguistic knowledge (MK) on the technicality of the headlines. Couched within Relevance Theory, including the interlarding theories of Communicative Competence and Monitor Hypothesis, this study investigated 80 students' technical knowledge on selected 35 headlines vis-à-vis the students' academic disciplines and exposure to the headlines/news articles. The study employed a Grammaticality Judgment Test (GJT) by Schütze (1996) following Noam Chomsky's competence/performance distinction. The results showed the dearth of the students' knowledge on the technical rules of the headlines, which only fared around 70.66% accuracy. Likewise, the results showed that those who were never exposed to the headlines had a significantly lower mean score as compared to those with exposure to the headlines. Poor cognizance of the semantics-syntax of the headlines statistically cuts across eight academic disciplines and exposure to news articles. Overall, the students' understanding of the headlines seems to be shaped by their explicit knowledge and grammaticality judgment about the technicalities of the headlines. By and large, such results may be an indication of the students' experiences of semantic ambiguities of the headlines. We put forth the dire need for the re-introduction of 'Journalism' course across educational levels in a language classroom given today's rapid pervasiveness and breadth of digitalism. Students' lack of MK on the technicality of the headlines can impinge on their understanding of the semantics and the actual story-level depictions of the news.